The Impact of Refugees on the Social Economic Development of the Host Communities: A Case Study of Nyakabande Refugee Transit Kisoro District. - Ngabire, Robert (Kabale University, 2023)
The study investigated the impact of refugees on the socio-economic development of the host communities in the Nyakabande sub-county. The study was set to investigate the economic retain between the refugees and the host communities and the economic and social effects of refugees and the host communities. Primary data was gathered using the questionnaire and interview guide, and secondary data, was obtained by analyzing the related literature from the books, newspapers, and reports. The study was composed of 192 respondents selected using random sampling technics. The respondents included the LCI chairperson and their committee members. The study established that refugees bring productivity in the host communities, complement the job market, stimulate the economy complement market demand for goods and services, employment opportunities to the people around the transit areas and refugee camps which rises the standard of living, donations by the host communities Environmental degradation, increased demand for goods and services which rises the standards of living of the host communities, land grabbing, sharing of social facilities, cooperation of social functioning and insecurity of the host communities were cited to be some of the social relationship between the refugees and the host communities, deforestation, increased demand for goods and services, infrastructural development, theft, social ills like prostitution, competition for properties, compromised resources. The study concluded that there is a need to understand that the environment in which refugees live is an important aspect of their social well-being and the host communities, Furthermore from the discussion, it becomes clear that social socioeconomic impact of refugees is an important matter that affects the host communities and affect both the refugees and the locals The researcher recommended that there should be measures and guidelines that guide the refugees on how they need to handle themselves in the host communities, this will help to stop them from raising resources. Which are not meant for them and will presumably have a good relationship with the host communities.